Merdeka Belajar: Akselerasi Pembelajaran Sesuai Bakat dan Minat - Resti Ramdayani; Masduki Asbari; Erisha Nurfatimah (AGUSPATI RESEARCH INSTITUTA, 2023)
The aim of this discussion is to ensure that every student has access and the opportunity to learn according to their interests and potential, so that they can achieve optimal learning outcomes and contribute to the development of themselves, society and the country as a whole. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to oral narratives from the channel The Ministry of Education and Culture's YouTube entitled